2006
DOI: 10.1111/j.1365-2486.2006.01157.x
|View full text |Cite
|
Sign up to set email alerts
|

Do geographic distribution, niche property and life form explain plants' vulnerability to global change?

Abstract: International audienceWe modelled the future distribution in 2050 of 975 endemic plant species in southern Africa distributed among seven life forms, including new methodological insights improving the accuracy and ecological realism of predictions of global changes studies by: (i) using only endemic species as a way to capture the full realized niche of species, (ii) considering the direct impact of human pressure on landscape and biodiversity jointly with climate, and (iii) taking species' migration into acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
234
3
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(251 citation statements)
references
References 83 publications
10
234
3
4
Order By: Relevance
“…12,13 Modelling studies have indicated that the Succulent Karoo may suffer a reduction in spatial extent of up to 40% as well as consequent reductions in the abundance and diversity of endemic species as a result of changes in temperature and rainfall. 14,15 In terms of individual species' responses to climate change, a study by Broennimann et al 16 found that geophytes and succulents, which make up over half of plant species in Namaqualand, were particularly vulnerable to climate change. They predicted a minimum decline in species richness of 41% for the Succulent Karoo biome.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Modelling studies have indicated that the Succulent Karoo may suffer a reduction in spatial extent of up to 40% as well as consequent reductions in the abundance and diversity of endemic species as a result of changes in temperature and rainfall. 14,15 In terms of individual species' responses to climate change, a study by Broennimann et al 16 found that geophytes and succulents, which make up over half of plant species in Namaqualand, were particularly vulnerable to climate change. They predicted a minimum decline in species richness of 41% for the Succulent Karoo biome.…”
Section: Introductionmentioning
confidence: 99%
“…As well as the level of climatic niche conservatism via phenological changes, this study focused on traits that can affect species' range shifts considered by other studies [32,33]: (i) dispersal abilities, (ii) niche breadth (reflecting ecological generalization) and (iii) perennation (reflecting generation time). Mean seed mass (mg) and seed releasing height (m), both measures of dispersal abilities, were derived from the LEDA Traitbase [34].…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of studies have used bioclimate envelope modelling to predict the 56 future biogeographic ranges of species (Bakkenes et al, 2002;Broennimann et al, 2006;Peterson et al, 2002;Schwarz et al, 2006;Thuiller et al, 2005). Refined 58 methods are being developed that entail the use of increasingly sophisticated statistics (e.g.…”
mentioning
confidence: 99%